DIGITAL TRANSFORMATION IN THE AUTOMOBILE INDUSTRY: A TECHNICAL ANALYSIS OF CUSTOMER SUCCESS ENHANCEMENT - Gaurav Gupta, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article presents a comprehensive analysis of digital transformation in the automotive industry, focusing on customer success enhancement through technological innovation. The article examines the implementation of advanced technologies across the automotive value chain, from manufacturing to post-purchase services. Through analysis of industry data, the article demonstrates that digital transformation initiatives have led to significant improvements in customer satisfaction and operational efficiency. The article investigates four key areas: IoT integration and vehicle connectivity, data analytics infrastructure, digital customer journey implementation, and security considerations. The article reveals that connected vehicle platforms process the average data per driving hour, while AI-powered customer support systems accuracy in natural language processing. The article also addresses critical security challenges and future technological directions, highlighting the industry's move toward quantum-resistant security protocols and cloud-native architectures. This article provides valuable insights into the technological advancement of the automotive sector and its impact on customer experience enhancement.